Cost effective energy and carbon emissions optimization in building renovation - Almeida, Manuela Guedes de (2012)
In order to mitigate climate changes induced by human action, the European Union settled a long term goal of reducing, up to 2050, the carbon emissions to 80 to 95% of 1990 values. At the level of the built environment it is expected to reduce carbon emissions to about 90% of the values of 1990 in that period. In order to promote this achievement, EU established the “nearly-zero energy” buildings concept that emerged in the context of the EPBD recast. This directive determines that by 31 December 2020, all new buildings must be nearly zero-energy buildings and all member states must develop policies and take measures to stimulate the transformation of the building stock also into nearly zero-energy buildings. In the actual context, this is a major challenge since there isn’t yet enough knowhow to do it and the existing standards and regulations regarding energy consumption are mainly focused on new buildings and do not respond effectively to the numerous constraints of the existing ones. It is then urgent to develop new renovation approaches that take into consideration the characteristics and limitations of existing buildings as well as to develop tools and good-practices guides, hold on appropriate, applicable and cost effective technologies, to support the different decision makers involved in this sector. The great challenge is to find sustainable ways of renovate in a cost-effective and massive way the huge and high energy consumer building stock.